RANCANG BANGUN SISTEM INFORMASI ARSIP AKTA NOTARIS PADA KANTOR NOTARIS DAN PPAT BERBASIS WEBSITE - I Gusti Ayu Komang Anom Arnita; I Putu Dody Suarnatha; I Made Agus Oka Gunawan (Universitas Tabanan, 2025)
The advancement of information technology has driven transformation in archive management, including within notary offices. Manual archiving systems, which are still commonly used, pose several issues such as data loss risks, limited accessibility, and inefficiencies in document retrieval. This study aims to develop a web-based notarial deed archiving information system to address these challenges. The development process adopts the Waterfall software development model, consisting of five stages: requirement analysis, system design, implementation, testing, and maintenance. The design phase includes Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and user interface layouts. The system is implemented using web-based technologies and includes core features such as login, dashboard statistics, deed input and management, document search by category and date, and print functionality. Testing is conducted using the black-box testing method, confirming that all functional requirements perform as expected. As a result, the proposed information system improves effectiveness, efficiency, and data security in managing notarial documents while ensuring compliance with applicable legal regulations.